Little Red Cowboy Hat - Lowell, Susan, 1950-; Cecil, Randy (New York : H. Holt and Co., 2000)
Presents a Southwestern adaptation of the classic fairytale "Little Red Riding Hood" in which Little Red rides her pony Buck to Grandma's ranch with a jar of cactus jelly in the saddlebag.
Booklist
Elem. School Library Collection
School Library Journal starred
3.5
K-3
K-3
Keywords: Folklore; Folklore